Excedente, valor y distribución en las teorías clásica y marxista del crecimiento - Sancho, Alejandro (1997)
This article develops the classical and Marxist theory of growth, establishing their basic links and main features, that is, the bond among their theories of value, distribution, accumulation and growth, centered around the concept of surplus, and the key role of the sphere of production in the determination of those theories. The exposition tries to show up the unity, continuity and progressiveness theoretical-analytic among the theories of the Physiocrats, Smith, Ricardo and Marx. In all of them it is analyzed the meaning of the saving-investment process and its relation with the growth, specially their stance with regard to the Say's Law.